USE OF DIDACTIC GAMES IN GEOGRAPHY CLASSES AND ITS EFFECTIVENESS - F.S.Meliboyeva; G.M.Begimqulova (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article explains the positive aspects of using creative games in the process of globalization of education and ways to effectively use interesting games in geography lessons to increase students' interest in geographic knowledge